Sympathetic Activation in Hypertensive Chronic Kidney Disease – A Stimulus for Cardiac Arrhythmias and Sudden Cardiac Death? - Kiuchi, Márcio Galindo; Ho, Jan K.; Nolde, Janis Marc; Gavidia, Leslie Marisol Lugo; Carnagarin, Revathy; Matthews, Vance B.; Schlaich, Markus P. (Frontiers in Physiology, 2020)
Studies have revealed a robust and independent correlation between chronic kidney disease (CKD) and cardiovascular events, including death, heart failure, and myocardial infarction. Recent clinical trials extend this range of adverse cardiovascular events to include ventricular arrhythmias and sudden cardiac death. Furthermore, other studies suggest that structural remodeling of the heart and electrophysiological alterations are a common occurrence in this population. These processes are likely contributors to the increased risk of cardiac arrhythmias in patients with CKD and may be useful indicators to identify patients who are at increased risk of sudden cardiac death (SCD). Sympathetic overactivity is associated with increased cardiovascular risk, specifically in CKD patients, and is a hallmark of a hypertensive state, occurring early in the clinical course of hypertension. Sympathetic hyperactivity is already evident at the earliest clinical stage of CKD and is directly related to the progression of renal failure a most pronounced in those with end-stage renal disease. Sympathetic efferent and afferent neural activity in kidney failure is a crucial mediator for the maintenance and progression of the disease. Here, we will revisit the role of the feedback loop of the sympathetic neural cycle in the context of CKD and how it may aggravate several of the risk factors responsible for causing SCD. Targeting the overactive sympathetic nervous system therapeutically, either pharmacologically or with newly available device based approaches, may prove to be a pivotal intervention to curb the substantial burden of cardiac arrhythmias and SCD in the high-risk population of patients with CKD.